How do fungal partners affect the evolution and habitat preferences of mycoheterotrophic plants? A case study in Gastrodia. Issue 2 (2nd February 2016) - Kinoshita, Akihiko; Ogura‐Tsujita, Yuki; Umata, Hidetaka; Sato, Hiroki; Hashimoto, Toshimasa; Yukawa, Tomohisa
Abstract : PREMISE OF THE STUDY: Since mycoheterotrophic plants (MHPs) completely depend on their mycorrhizal fungi for carbon, selection of fungal partners has an important role in the speciation of MHPs. However, the causes and mechanisms of mycobiont changes during speciation are not clear. We tested fungal partner shifts and changes in mycorrhizal specificity during speciation of three closely related MHPs— Gastrodia confusa ( Gc ), G. pubilabiata ( Gp ), and G. nipponica ( Gn ) (Orchidaceae)—and correlations between these changes and the vegetation types where each species grows. METHODS: We investigated the diversity of mycobionts of the three species by sequencing nrDNA ITS, and the sequence data were subjected to test changes in fungal specificity and fungal partner shifts among the three species. Furthermore, we conducted multivariate analysis to test for differences in mycobiont communities of vegetation types where each species grows. KEY RESULTS: Two saprobic Basidiomycota, Marasmiaceae and Mycenaceae, were dominant fungal partners of the three species, and Gn was simultaneously associated with the ectomycorrhizal Russulaceae and Sebacinaceae. Although mycobiont composition differed among the three species, they also sometimes shared identical fungal species. Multivariate analysis revealed that mycobiont communities of the three species in bamboo thickets differed significantly from those in other vegetation types. CONCLUSIONS: Fungal partner shifts are not necessarily associated with the evolution of MHPs, and fungal specificity of Gc and Gp was significantly higher than that of Gn, implying that the specificity fluctuates during speciation. Further, Gc exclusively inhabits bamboo thickets, which suggests that adaptation to particular fungi specific to bamboo thickets triggered speciation of this species.